An architecture for extensible wireless LANs - Murty, Rohan; Padhye, Jitu; Wolman, Alec; Welsh, Matt (2008)
This paper presents Trantor, an architecture for extensible wireless LANs. Trantor enables rapid innovation by removing standardization from the path of introducing new technologies. This is achieved largely by moving the intelligence away from wireless clients and into the infrastructure. In addition to providing extensibility, this approach can also help improve overall network performance through the use of global and historical information. Trantor enables network administrators to impose local policies thereby easing the task of wireless LAN management. In this paper we outline the motivation, vision, and architecture of Trantor.